2013
DOI: 10.1371/journal.pone.0073216
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Value-Sensitive Decision-Making

Abstract: We present a dynamical systems analysis of a decision-making mechanism inspired by collective choice in house-hunting honeybee swarms, revealing the crucial role of cross-inhibitory ‘stop-signalling’ in improving the decision-making capabilities. We show that strength of cross-inhibition is a decision-parameter influencing how decisions depend both on the difference in value and on the mean value of the alternatives; this is in contrast to many previous mechanistic models of decision-making, which are typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
220
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 121 publications
(241 citation statements)
references
References 37 publications
21
220
0
Order By: Relevance
“…On the one hand, this may lead to errors in the decision making if the system happens to be in the basin of attraction of the inferior choice. On the other hand, as also noted in [11], larger cross-inhibition rates lead to increased decision speed (see Figure 5(a)). Similar dynamics can be observed for different values of θ < π, for which we observed that smaller differences between the alternatives sometimes lead to the wrong choice, as predicted by the macroscopic model (see supplementary material http://iridia.ulb.ac.be/supp/IridiaSupp2014-005/sm.pdf).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…On the one hand, this may lead to errors in the decision making if the system happens to be in the basin of attraction of the inferior choice. On the other hand, as also noted in [11], larger cross-inhibition rates lead to increased decision speed (see Figure 5(a)). Similar dynamics can be observed for different values of θ < π, for which we observed that smaller differences between the alternatives sometimes lead to the wrong choice, as predicted by the macroscopic model (see supplementary material http://iridia.ulb.ac.be/supp/IridiaSupp2014-005/sm.pdf).…”
Section: Resultssupporting
confidence: 76%
“…It is worth noting that this model does not require any explicit comparison of the alternatives' quality by the single individuals. The quality value of the two alternativeshereafter labelled v A and v B -is instead encoded in the transition rates (e.g., through value-dependent discovery or recruitment rates [11]): different-quality alternatives correspond to biased transition rates, while same-quality alternatives to unbiased ones. Overall, the collective decision is based purely on the system dynamics resulting from individual-to-individual interactions.…”
Section: Biological Inspiration and Theoretical Modelsmentioning
confidence: 99%
See 3 more Smart Citations